ANALISIS PERILAKU VOICE SEBAGAI MODERATOR HUBUNGAN ANTARA KETIDAKPUASAN KERJA DAN KREATIVITAS - Askar Yunianto (Jurnal Bisnis dan Ekonomi, 2007)
This study examined the effect of job dissatisfaction to creativity, as main effect. And also investigate whether Commitment Continuance and some of Contextual variables could significantly moderate the relationship between job dissatisfaction and creativity The sample research was employees (Educative and Administrative Employee) at the Private High School in Semarang. Of the 225 questionnaire were distributed, 213 questionnaire were returned to the researcher (response rate 94%). Twenty two of these were excluded from the data analysis because of missing value, not give the same code and no code, leaving sample of 184.It was hypothesized that Job Dissatisfaction would affect significantly to Creativity. It was also hypothesized that Commitment Continuance and some of Contextual Variables simultaneously would significantly moderated the relationship between Job Dissatisfaction and Creativityi The result of Simple Rgression Analysis indicated that Job Dissatisfaction had no significant effect on Creativity. Based on Moderated Regression Analysis, the results were not supported the predicted moderating effect of Continuance Commitment and Some of Contextual Variables simultaneously in relationship between Job Dissatisfaction to Creativity. The result warrant future research. Keywords :Voice behavior, Creativity, Job Dissatisfaction, Continuance Commitment, Useful Feedback from Coworkers,Coworker’s Helping and Supporting, Perceived Organizational Support, and Supervisory Support